PENATALAKSANAAN FISIOTERAPI PADA KETERBATASAN AKTIVITAS FUNGSIONAL AKIBAT ADANYA GANGGUAN FUNGSI RESPIRASI OLEH KARENA SESAK NAPAS DAN BATUK E.C PPOK: CASE REPORT - I Gede Eka Juli Prasana; Ariezta Jeviana; Ni Luh Anita Chandra Dewi; Wirawan Tantra Pratama; Ida Ayu Jelantik Ari Parmitha; Putu Ayu Bintang Anjali (Prodi Fisioterapi, Fikes, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Background: The prevalence of Chronic Obstructive Pulmonary Disease (COPD) in Indonesia has shown a significant increase from year to year. A hallmark of COPD is chronic obstruction of the airways. Rehabilitation in patients with COPD is necessary to prevent further complications and to restore respiratory function and daily activity capacity. Objective: This case report aims to explore the physiotherapy management of functional activity limitations caused by respiratory dysfunction due to shortness of breath and coughing resulting from COPD. Method: This program was carried out directly on a respondent with respiratory dysfunction characterized by shortness of breath and coughing due to COPD. The therapy was administered in three sessions. Assessments included muscle strength using the Manual Muscle Test Grading, dyspnea using the Borg Scale, lung volume through thoracic cage expansion and metline measurements, risk of pressure sores using the Braden Scale, and functional activity using the Barthel Index. Results: After three therapy sessions, there was a decrease in dyspnea scale from 2/10 to 0.5/10. Additionally, lung volume showed an increase in the xiphoid process area with a difference of 2 cm, although it had not yet reached the normal category. Conclusion: Physiotherapy management in a patient with Chronic Obstructive Pulmonary Disease (COPD) demonstrated positive outcomes. Through the application of techniques such as breathing control, pursed-lip breathing, segmental breathing, and diaphragmatic breathing over three sessions, there was a significant reduction in shortness of breath and an improvement in lung volume. Keywords: COPD, breathing control, pursed-lip breathing, segmental breathing, forced expiratory breathing, thoracic cage expansion, positioning.